Livelihood strategies and household income of a paddy farming community in northwest Selangor, Malaysia / Siti Badariah Saiful Nathan, Mohd Rosli Mohamad - Saiful Nathan, Siti Badariah (Faculty of Business and Management, Universiti Teknologi MARA, Selangor, 2014)
The importance of non-farm employment to rural households was widely acknowledged. However, empirical evidence on the relationship between household assets and non-farm activities is hardly found. This study identifies the determinants of a household’s selection of a livelihood strategy. Results from multinomial logistic regression showed that the size of cultivated land was a significant factor for a livelihood strategy. The average education of working members, the share of other non-farm income and the availability of credit were also the significant determinants of a diversified livelihood strategy. This indicates that any policy intervention should be distinctive for certain group of paddy farming households.